Root canal curvature as a prognostic factor influencing the diagnostic accuracy of radiographic working length determination and postoperative canal axis modification: an in vitro comparative study - Bestoon Mohammed Faraj (BMC, 2021)
Abstract Background Radiographic analysis of tooth morphology is mandatory for accurate calibration of the degree of canal curvature angle and radiographic working length to its real dimensions in case difficulty assessment protocols. This study aimed to determine the impact of the degree of root canal curvature angle on maintaining the real working length and the original canal axis of prepared root canals using a reciprocating rotary instrumentation technique. Methods Radiographic image analysis was performed on 60 extracted single-rooted human premolar teeth with a moderate canal curvature (10°-25°) and severe canal curvature (26°-70°). Working length and longitudinal canal axis were determined using cone-beam computed tomography (CBCT) and digital periapical radiography. The real canal length was determined by subtracting 0.5 mm from the actual canal length. Root canals were prepared using the WaveOne Gold reciprocating file (Dentsply Maillefer, Ballaigues, Switzerland). Results There was no significant relation of the degree of canal curvature angle to the accuracy of radiographic working length estimated on CBCT and digital periapical radiographic techniques (P > 0.05). Postinstrumentation changes in the original canal axis between moderate and severe canal curvature angles, assessed on CBCT and periapical digital radiographic images were statistically non-significant (P > 0.05). Conclusions A standardized digital periapical radiographic method performed similarly to the CBCT technique near to its true working length. No significant interaction exists between the diagnostic working length estimation, postoperative root canal axis modification, and the degree of canal curvature angle, using reciprocating rotary instrumentation technique.